2018
DOI: 10.31234/osf.io/p7nes
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Early lexical influences on sublexical processing in speech perception: Evidence from electrophysiology

Abstract: Contextual information influences how we perceive speech, but it remains unclear at which level of processing contextual information merges with acoustic information. Theories differ on whether early, sublexical speech processing levels are strictly feed-forward or are influenced by semantic and lexical context. Studies using behavioral responses have shown contextual factors influence sublexical judgments but are unable to pinpoint whether context biases responses by modulating sublexical processing or later… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 0 publications
4
9
0
Order By: Relevance
“…Adaptation studies-in which continuum sounds are presented repetitively and/or in serial order (Eimas and Corbit, 1973;Miller, 1975 causing a boundary shift in the direction toward the un-adapted detector at the polar end of the continuum (Rozsypal et al, 1985). As confirmed empirically, larger boundary shifts would be expected for less strongly categorized continua (Rozsypal et al, 1985), e.g., vowels vs. stop consonants (Altmann et al, 2014), acoustically degraded speech (Bidelman et al, 2020;, and for ambiguous speech tokens as shown here and previously (Ganong, 1980;Gow et al, 2008;Lam et al, 2017;Myers and Blumstein, 2008;Noe and Fischer-Baum, 2020).…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…Adaptation studies-in which continuum sounds are presented repetitively and/or in serial order (Eimas and Corbit, 1973;Miller, 1975 causing a boundary shift in the direction toward the un-adapted detector at the polar end of the continuum (Rozsypal et al, 1985). As confirmed empirically, larger boundary shifts would be expected for less strongly categorized continua (Rozsypal et al, 1985), e.g., vowels vs. stop consonants (Altmann et al, 2014), acoustically degraded speech (Bidelman et al, 2020;, and for ambiguous speech tokens as shown here and previously (Ganong, 1980;Gow et al, 2008;Lam et al, 2017;Myers and Blumstein, 2008;Noe and Fischer-Baum, 2020).…”
Section: Discussionsupporting
confidence: 74%
“…Our data are best cast in terms of interactive rather than serial frameworks of speech perception as in the TRACE model of spoken word recognition (McClelland and Elman, 1986). As confirmed empirically (Ganong, 1980;Gow et al, 2008;Lam et al, 2017;Myers and Blumstein, 2008;Noe and Fischer-Baum, 2020), these models predict stronger lexical biasing when speech sounds carry ambiguity. Indeed, neural correlates of the Ganong effect were most evident at the midpoint of our speech continua, where word influences exert their strongest effect.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations